Genetic risk variants as therapeutic targets for Crohn's disease. (3rd April 2017) - Gabbani, Tommaso; Deiana, Simona; Marocchi, Margherita; Annese, Vito
ABSTRACT: Introduction : The pathogenesis of Inflammatory bowel diseases (IBD) is multifactorial, with interactions between genetic and environmental factors. Despite the existence of genetic factors being largely demonstrated by epidemiological data and several genetic studies, only a few findings have been useful in term of disease prediction, disease progression and targeting therapy. Areas covered : This review summarizes the results of genome-wide association studies in Crohn's disease, the role of epigenetics and the recent discovery by genetic studies of new pathogenetic pathways. Furthermore, it focuses on the importance of applying genetic data to clinical practice, and more specifically how to better target therapy and predict potential drug-related toxicity. Expert opinion : Some genetic markers identified in Crohn`s disease have allowed investigators to hypothesize about, and in some cases, prove the usefulness of new specific therapeutic agents. However, the heterogeneity and complexity of this disease has so far limited the daily clinical use of genetic information. Finally, the study of the implications of genetics on therapy, either to predict efficacy or avoid toxicity, is considered still to be in its infancy.